Preliminary Indoor Radon Measurements Near Faults Crossing Urban Areas of Mt. Etna Volcano (Italy) - Neri, Marco; Giammanco, Salvatore; Leonardi, Anna (Frontiers in Public Health, 2019)
The slopes of Etna are crossed by numerous active faults that traverse various towns and villages. These faults pose a two-fold problem for the local people: on one hand, they cause frequent damage to houses and breakage of roads, while on the other they constitute a preferential route for the rising of crustal and sub-crustal gases, including radon, towards the surface. Various recent studies on the volcano confirm a high level of radon degassing measured both in the soil (> 10,000 Bq/m3), and inside homes (> 2,000 Bq/m3). For this reason, we felt the need to deepen our knowledge on the radon present in the Etnean area, focusing in particular on indoor radon pollution that, as widely recognised, is among the main causes of cancer largely (but not exclusively) of the respiratory system. Firstly, since 2005 we made a broad surface survey that revealed very high radon emissions from soils near active faults on Etna. Typical background soil activity on Etna were <1000 Bq/m3, whereas in areas of stronger soil degassing, activity values up to ~60,000 Bq/m3 were measured. Furthermore, since late 2015 we have performed continuous indoor radon monitoring inside seven houses, some of which located close to degassing faults on the eastern, southern and south-western flanks of the volcano. Indoor radon concentration varied according to the season of the year, but above all, they changed according to the geology and tectonic setting of the substratum of the monitored houses. In one case, indoor radon concentration reached 3,549 Bq/m3 and remained > 1,000 Bq/m3 for several consecutive months, highlighting a potential health problem for those living in such environments. In other cases, the construction features of the houses and/or the materials used seemed to play an important role in the mitigation of indoor radon accumulation, even in the presence of intensely degassing soils. These preliminary data demonstrate the need to deepen the studies, extending indoor radon measurements to other urban areas, in order to monitor the health hazard for the Etna population, amounting to about one million people.